2016
DOI: 10.1063/1.4940092
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of concrete compression strength using ultrasonic pulse velocity

Abstract: Correlation between compressive strength and ultrasonic pulse velocity of high strength concrete incorporating chopped basalt fibre AIP Conference Proceedings 1669, 020010 (2015) Abstract. The relationship of ultrasonic stress waves transmitted along direct and indirect paths in concrete samples was investigated. Tests were conducted on plain concrete slabs from different grades of 15, 25, 30, 40 and Ultrahigh Performance Concrete that have dimensions of 750mm x 150mm x 150 mm. Direct ultrasonic pulse velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…En la figura # 3 se muestra el comportamiento de la VPU en función del tiempo de estufado para la dosificación 1 de baja resistencia a la compresión, que se corresponde con un nivel de porosidad mayor, lo cual se muestra en que el tiempo de secado necesario para alcanzar un valor asintótico en la dosificación 1 es de 48 horas y en la dosificación 4 es de 30 horas. El objetivo fundamental de la aplicación del método ultrasónico en el estudio del concreto es correlacionar el valor de la VPU con la resistencia a la compresión [Azreen M. N;Pauzi I.;M, Nasharuddin I.;Haniza M. M, Akasyah J.;Karsono A. D, and Yen Lei V. (2016) ; Ferreira, Almir P. and Castro, Protasio F, 2000, Quintero L,A 2014, Quintero L,A.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…En la figura # 3 se muestra el comportamiento de la VPU en función del tiempo de estufado para la dosificación 1 de baja resistencia a la compresión, que se corresponde con un nivel de porosidad mayor, lo cual se muestra en que el tiempo de secado necesario para alcanzar un valor asintótico en la dosificación 1 es de 48 horas y en la dosificación 4 es de 30 horas. El objetivo fundamental de la aplicación del método ultrasónico en el estudio del concreto es correlacionar el valor de la VPU con la resistencia a la compresión [Azreen M. N;Pauzi I.;M, Nasharuddin I.;Haniza M. M, Akasyah J.;Karsono A. D, and Yen Lei V. (2016) ; Ferreira, Almir P. and Castro, Protasio F, 2000, Quintero L,A 2014, Quintero L,A.…”
Section: Resultsunclassified
“…Un método eficaz para dar respuesta a estas necesidades es el método de la velocidad del pulso ultrasónico (VPU). [Kathleen W., et all,1999;Andej G, 1990;Malhotra VM ,2004;Azreen M. N;Pauzi I.;M, Nasharuddin I.;Haniza M. M, Akasyah J.;Karsono A. D, and Yen Lei V. (2016)] Dentro del campo de aplicación de la velocidad del pulso ultrasónico en el estudio de las propiedades del hormigón, las más divulgadas son las investigaciones que relacionan la VPU con las propiedades físico-mecánicas del hormigón sobre todo la resistencia a la compresión [Contreras A.;; Cruz Benedetti J E; Martínez Acosta L; López Ramos Á; Lakah Durango J A; Ceballos Díaz C; (2016).]…”
Section: Introduccionunclassified
“…3. It is recommended to build new models to decrease zero values of fly ash, silica fume, BFS, steel fiber and superplasticizer to adjust the model and agree with Jain et al[12]…”
mentioning
confidence: 80%
“…In general, ultrasonic pulse velocity (UPV) tests are performed by direct measurement (opposite faces) or indirect measurement (along the surfaces). 14 According to the Azreen et al, 9 direct measurement method shows a good correlation for estimating the compressive strength of concrete using cylinder core specimen. Therefore, direct measurements were carried out using a cylindrical specimen with the dimension of 100 mm in diameter and 200 mm in height in this study.…”
Section: Experimental Testsmentioning
confidence: 99%
“…Test results indicated that compressive strength of concrete by the both tests decreased steadily with the increase of temperature, and it can be concluded that UPV test is reliable to investigated the quick assessment of compressive strength on fire affected concrete with relatively less exposure time. Azreen et al 9 investigated UPV values with a total of 70 cube concrete samples (150 mm 3 150 mm 3 150 mm) and seven beam samples (750 mm 3 150 mm 3 150 mm) by direct and indirect paths. Direct UPV Tests were performed between the top and the bottom surfaces of the concrete specimen and indirect tests were conducted along the surface.…”
Section: Introductionmentioning
confidence: 99%